Relationship between active deformation, rheology and magmatism in a continental rift context : Seismological study of the North Tanzanian Divergence, East African Rift - (:unkn) unknown (My University, 2009)
Rifting a continent requires sufficient tensional stresses to deform continental plates (far-field plate motions, asthenospheric upwelling, traction form asthenospheric convection) and is controlled by different factors as rheology and lithospheric inheritance. Magmatic (dyking) and tectonic (faulting, aseismic creep) processes are involved in this deformation and their relative importance is not well known and appears to change from one rift to another. The North Tanzanian Divergence (NTD), East African Rift, offers quite favorable conditions to better understand how these processes and factors interact : indeed, it represents the early stage of rifting and is characterized by a sharp change of volcanic and morphotectonic styles. From a local seismological network deployed for 6 months in the NTD (35 stations, SEISMO-TANZ'07), we have recorded earthquakes in order to study their triggering mechanisms, crustal strength, strain and stress fields, and seismic anisotropy. Earthquakes are essentially clustered in the NTD central branch, south of lakes Natron (south of Gelai volcanoe) and Manyara. Magmatic and tectonic processes are both involved in the deformation observed at Gelai : dyking, aseismic slip, faulting (culmination with a Mw 5.9) in the upper crust. The direction of these geological structures is oblique compared with the ~N-S orientation of the rift and parallel to the NE-SW inherited structures, where the rift is partially developping (Eyasi rift). The Manyara cluster is deep (~20-35 km) and associated with significant NE-SW strike-slip faulting. It illustrates the south/southwest rift propagation along the Natron-Manyara-Balangida central branch and the craton buried contact. The minimum principal stress in the area is WNW-ESE and the associated stress field is transtensive. Fluids may play a significant role in the triggering of this deep and long lasting seismic sequence. The influence of the structural inheritance on the magmatic and tec
Keywords: African Research